VIRTUAL REALITY AND MODERN SCIENCE - Khaidarova Akida Khurram kizi (Journals Park Publishing, 2022)
The topic of virtual existence is relatively new in research circles. The term "virtual being" was first used by a number of modern researchers as an information technology term, and is currently being studied as a historical and philosophical aspect. Modern authors approach the problem of virtuality from opposite positions. As a result, the concept of virtuality has become more complex. Currently, virtuality is considered as a phenomenon created by man in an artificial environment.
Keywords: virtual being; phenomenon; post-industrial society